Translation of Food and Beverage Names from Thai to English : A Case Study in Phitsanulok - Seedang, Warirat; Wongwattana , Unchalee; Kitikanan, Patchanok (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2023)
This study aimed to analyze translation strategies of food and beverage names from Thai to English and seek for translation guidelines of the food and beverage names from Thai to English. The data were 2,586 food and beverage translated names (2,302 food names and 284 beverage names) from 31 restaurants in Phitsanulok located in tourist areas and found by Thai owners in 2018. For data analysis, the translation theory framework of Newmark (1988) was applied for the analysis of translation strategies. Also, the syntactic analysis was considered based on Givón (2001 as cited in Wongwattana, 2008). The results reveal that in overall 6 translation strategies were used in the translation of food and beverage names from Thai to English: communicative, semantic, literal, free, adaptation, and faithful. Besides, other forms of translation were also found, including incomplete translation, translation strategies mixed with transliteration, transliteration, and mixed translation strategies. For the translation guidelines suggested for the food and beverage names, most names translated in English (by 96% of all names) were incomplete since both Thai and foreign food cultures have not been seriously taken into account.